1982
DOI: 10.1177/0013916582145003
|View full text |Cite
|
Sign up to set email alerts
|

Physical Enclosure, Type of Job, and Privacy in the Office

Abstract: Office employees from three job groups-including 88 secretaries, 44 bookkeepers and accountants, and 22 office managers and administrators-completed a questionnaire and had their workspaces measured for the number of partitions, the amount of floorspace, the number of people in the room, and other features. The best single predictor of rated privacy of workspaces for all job groups was the number of partitions around the workspace. Occupants of private offices rated their workspaces most private, but office ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 7 publications
1
66
1
Order By: Relevance
“…Privacy is a key requirement of workplaces and Sundstrom et al (1982b) reported an approximately linear increase in perceived privacy with each number of enclosed sides around the workspace. Maher and von Hippel (2005), however, found that the number of partitions were not correlated with perceived privacy but they did find a positive correlation between the height of partitions and perceived privacy.…”
Section: User Perceptions and Workplace Productivitymentioning
confidence: 99%
“…Privacy is a key requirement of workplaces and Sundstrom et al (1982b) reported an approximately linear increase in perceived privacy with each number of enclosed sides around the workspace. Maher and von Hippel (2005), however, found that the number of partitions were not correlated with perceived privacy but they did find a positive correlation between the height of partitions and perceived privacy.…”
Section: User Perceptions and Workplace Productivitymentioning
confidence: 99%
“…Problems include loss of privacy, loss of confidentiality, distractions and interruptions (Sundstrom et al, 1982;Brill et al, 2001).…”
Section: Potential Bene¢ts and Constraintsmentioning
confidence: 99%
“…Most of the attention in the past few decades has been on open-plan offices and individual cognition (e.g. Bridger & Brasher, 2011;Roper & Juneja, 2008;Sundstrom, Town, Brown, Forman, & McGee, 1982). For example, Roper and Juneja (2008) argue that open-plan offices may heighten individual arousal and improve task performance via the social facilitation effect, but may also promote cognitive overload through crowding, office noise, distractions, and interruptions.…”
Section: Research Issuesmentioning
confidence: 99%
“…These findings encouraged researchers to focus on social and psychological antecedences to organisational behaviour, rather than physical ones (Sutton & Rafaeli, 1987) Although the physical work environment was mostly ignored within organisational behaviour throughout the middle of the twentieth century, in the 1970s and 1980s a number of key studies were published which examined the influence of office environments on coworker relations (Oldham & Brass, 1979;Oldham & Rotchford, 1983), communication (Allen, 1977;Hatch, 1987;Sundstrom, Herbert, & Brown, 1982), satisfaction (Oldham, 1988;Sundstrom, Burt, & Kamp, 1980) and productivity (Block & Stokes, 1989;Crouch & Nimran, 1989;Sundstrom & Sundstrom, 1986). The focus of these studies was on the ways in which aspects of the physical work environment, including proximity (Monge, Rothman, Eisenberg, Miller, & Kirste, 1985), privacy (Davis & Altman, 1976;Sundstrom, Town, Brown, Forman, & McGee, 1982) and office layout (Hedge, 1982;Oldham & Brass, 1979;Zalesny & Farace, 1987) influenced employee behaviour and attitudes. These studies laid the foundations for research in the 1990s and 2000s that focused more on the symbolic (Hatch, 1993), aesthetic (Strati, 1992) and meaningful (Rafaeli & Vilnai-Yavetz, 2004;VilnaiYavetz, Rafaeli, & Yaacov, 2005;Yanow, 1998) aspects of physical work environments, including their relationship with corporate culture (Hatch & Schultz, 1997).…”
Section: A Short History Of Research On Physical Work Environmentmentioning
confidence: 99%